All-solid-state battery
By using glass or glass ceramic containing lithium fluoride (LiF) as the cover layer and edge layer in an all-solid state battery, the battery's sensitivity to external moisture penetration is solved, and excellent moisture-proof function and reliability are achieved, preventing the deposition of lithium ion precipitates and extending the service life of the battery.
Patent Information
- Application Number
- CN202380065023.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-06
- Filing Date
- 2023-04-24
- Publication Date
- 2025-04-22
AI Technical Summary
All-solid state batteries are susceptible to external moisture penetration during operation, resulting in lithium ion precipitates depositing on the negative electrode and causing battery failure.
Glass or glass ceramics containing lithium fluoride (LiF) are used as the cover layer and edge layer. Through its low ion conductivity, high impedance resistance and low electron conductivity, it effectively prevents external moisture penetration and reduces interface resistance.
It improves the reliability and moisture-proof function of all-solid-state batteries, prevents the deposition of lithium ion precipitates, and extends the service life of the battery.
Smart Images

Figure CN119866568A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to an all-solid-state battery. Background Art
[0002] Recently, due to the need for miniaturization and long-term use of portable electronic devices, high-capacity batteries are required, and due to the development of wearable electronic devices, battery safety is also required. Therefore, the development of all-solid-state batteries using solid electrolytes instead of liquid electrolytes is actively underway.
[0003] Since all-solid-state batteries do not use flammable organic solvents, additional circuits for safety can be simplified. Therefore, all-solid-state batteries are expected to become a technology that can manufacture safe batteries with high capacity per unit volume.
[0004] In addition, compared with sulfide all-solid-state batteries that use sulfide electrolytes that react with oxygen and moisture in the air, the use of sulfide electrolytes with ionic conductivity (10 -2 S / cm) low ionic conductivity (10 -4 S / cm to 10 -6 Oxide all-solid-state batteries with oxide electrolytes of 2.5 K (S / cm) require high-temperature sintering processes but show excellent stability.
[0005] The stacked oxide all-solid-state battery is a micro-sized battery and can therefore be mounted on a substrate like a passive device, and furthermore, the stacked oxide all-solid-state battery is stable even when exposed to high temperatures in a reflow process for this purpose.
[0006] Research is being conducted on applying stacked oxide all-solid-state batteries to various fields, and in particular, the demand for all-solid-state batteries having excellent insulation and moisture-proof functions is increasing. Summary of the invention
[0007] Technical issues
[0008] An aspect of an embodiment provides an all-solid-state battery having improved reliability by effectively preventing penetration of external moisture, and having excellent moisture-proof function and excellent insulation to prevent battery failure caused by deposition of lithium (Li) ion precipitates on the negative electrode during battery operation.
[0009] However, the exemplary embodiments of the present invention are not limited thereto but may be applied in various ways within the scope of the technical ideas included in the exemplary embodiments.
[0010] Solution to the problem
[0011] The all-solid-state battery according to the embodiment includes: a unit stack including a solid electrolyte layer and a positive electrode layer and a negative electrode layer, wherein the positive electrode layer and the negative electrode layer are arranged so that the solid electrolyte layer is interposed between the positive electrode layer and the negative electrode layer; and a covering layer located on the outer surface of the unit stack. The covering layer includes glass containing lithium fluoride (LiF) or glass ceramic containing lithium fluoride (LiF).
[0012] The glass or the glass ceramic may include lithium fluoride (LiF) and lithium (Li) oxide.
[0013] The glass or the glass ceramic may include lithium fluoride (LiF) and lithium (Li) oxide, silicon (Si) oxide, boron (B) oxide, phosphorus (P) oxide, germanium (Ge) oxide, or a combination thereof.
[0014] Based on the total amount of the glass or the glass ceramic, the glass or the glass ceramic includes 5 mol% to 15 mol% of lithium fluoride (LiF), 20 mol% to 75 mol% of lithium (Li) oxide, 0 mol% to 70 mol% of silicon (Si) oxide, 0 mol% to 60 mol% of boron (B) oxide, 0 mol% to 50 mol% of phosphorus (P) oxide and 0 mol% to 80 mol% of germanium (Ge) oxide.
[0015] The solid electrolyte layer may include glass including lithium (Li) oxide and lithium chloride (LiCl) or glass ceramic including lithium (Li) oxide and lithium chloride (LiCl).
[0016] The glass or the glass ceramic included in the solid electrolyte layer may further include silicon (Si) oxide, boron (B) oxide, phosphorus (P) oxide, germanium (Ge) oxide, or a combination thereof.
[0017] The glass or the glass ceramic included in the solid electrolyte layer may include 3 mol % to 22 mol % of lithium chloride (LiCl), 20 mol % to 75 mol % of lithium (Li) oxide, 0 mol % to 70 mol % of silicon (Si) oxide, 0 mol % to 60 mol % of boron (B) oxide, 0 mol % to 50 mol % of phosphorus (P) oxide, and 0 mol % to 80 mol % of germanium (Ge) oxide, based on the total amount of the glass or the glass ceramic included in the solid electrolyte layer.
[0018] The cover layer may be provided on an outer surface of the positive electrode layer or the negative electrode layer located at the outermost side in the stacking direction of the unit stack.
[0019] A solid electrolyte layer may be provided between the cover layer and the positive electrode layer adjacent to the cover layer or between the cover layer and the negative electrode layer adjacent to the cover layer.
[0020] The unit stack may further include an edge layer disposed laterally adjacent to edges of the positive electrode layer and the negative electrode layer.
[0021] The edge layer may include glass containing lithium fluoride (LiF) or glass ceramic containing lithium fluoride (LiF).
[0022] According to another embodiment, an all-solid-state battery includes a unit stack, the unit stack including: a solid electrolyte layer; a positive electrode layer and a negative electrode layer, arranged so that the solid electrolyte layer is between the positive electrode layer and the negative electrode layer; and an edge layer, arranged laterally adjacent to the edges of the positive electrode layer and the negative electrode layer. The edge layer may include glass containing lithium fluoride (LiF) or glass ceramic containing lithium fluoride (LiF).
[0023] Based on the total amount of the glass or the glass ceramic, the glass or the glass ceramic may include 5 mol % to 15 mol % of lithium fluoride (LiF), 20 mol % to 75 mol % of lithium (Li) oxide, 0 mol % to 70 mol % of silicon (Si) oxide, 0 mol % to 60 mol % of boron (B) oxide, 0 mol % to 50 mol % of phosphorus (P) oxide and 0 mol % to 80 mol % of germanium (Ge) oxide.
[0024] The solid electrolyte layer may include glass or glass ceramic, wherein the glass or the glass ceramic includes 3 mol % to 22 mol % of lithium chloride (LiCl), 20 mol % to 75 mol % of lithium (Li) oxide, 0 mol % to 70 mol % of silicon (Si) oxide, 0 mol % to 60 mol % of boron (B) oxide, 0 mol % to 50 mol % of phosphorus (P) oxide, and 0 mol % to 80 mol % of germanium (Ge) oxide.
[0025] The edge layer may extend along an edge of an electrode active material layer of the positive electrode layer or the negative electrode layer.
[0026] The edge layer may be stacked on the solid electrolyte layer.
[0027] The all-solid-state battery may further include a cover layer on an outer surface of the unit stack, and the cover layer may include glass including lithium fluoride (LiF) or glass ceramic including lithium fluoride (LiF).
[0028] The all-solid-state battery may include a first external electrode and a second external electrode, wherein the first external electrode is disposed adjacent to one side of the unit stack and the cover layer and connected to the positive electrode layer, and the second external electrode is disposed adjacent to the other side of the unit stack and the cover layer and connected to the negative electrode layer.
[0029] The positive electrode layer may include a positive electrode collector and a positive electrode active material layer coated on at least one surface of the positive electrode collector.
[0030] The negative electrode layer may include a negative electrode collector and a negative electrode active material layer coated on at least one surface of the negative electrode collector.
[0031] The positive current collector may extend toward the one side of the unit stack and be connected to the first external electrode.
[0032] The negative electrode collector may extend toward the other side of the unit stack and be connected to the second external electrode.
[0033] According to another embodiment, an all-solid-state battery includes: a unit stack, including multiple solid electrolyte layers, multiple positive electrode layers and multiple negative electrode layers and multiple edge layers, the multiple positive electrode layers and the multiple negative electrode layers are alternately arranged and the multiple solid electrolyte layers are interposed between the multiple positive electrode layers and the multiple negative electrode layers, and the multiple edge layers are arranged laterally adjacent to the edges of the multiple positive electrode layers and the multiple negative electrode layers; a covering layer, located on the outer surface of the unit stack in the stacking direction of the multiple positive electrode layers and the multiple negative electrode layers; and a first external electrode and a second external electrode, arranged laterally adjacent to the unit stack and the covering layer and respectively connected to the multiple positive electrode layers and the multiple negative electrode layers, wherein the multiple edge layers, the covering layer, or both the multiple edge layers and the covering layer include glass containing lithium fluoride (LiF) or glass ceramic containing lithium fluoride (LiF).
[0034] According to another embodiment, an all-solid-state battery includes: a unit stack including a positive electrode layer and a negative electrode layer, a solid electrolyte layer, a first edge layer and a second edge layer, the solid electrolyte layer is arranged between the positive electrode layer and the negative electrode layer, the first edge layer is arranged on the end of the positive electrode layer, and the second edge layer is arranged on the end of the negative electrode layer; a covering layer is arranged on the outer surface of the unit stack in the stacking direction of the positive electrode layer and the negative electrode layer; and a first external electrode and a second external electrode are connected to the positive electrode layer and the negative electrode layer, respectively. One or more of the first edge layer, the second edge layer and the covering layer include fluorine (F).
[0035] A content of fluorine (F) in one or more of the first edge layer, the second edge layer, and the cover layer may be greater than a content of chlorine (Cl) in one or more of the first edge layer, the second edge layer, and the cover layer.
[0036] One or more of the first edge layer, the second edge layer, and the capping layer may further include one or more of silicon (Si) oxide, boron (B) oxide, phosphorus (P) oxide, germanium (Ge) oxide, and combinations thereof, and lithium.
[0037] The solid electrolyte layer may include chlorine (Cl).
[0038] The solid electrolyte layer may further include one or more of silicon (Si) oxide, boron (B) oxide, phosphorus (P) oxide, germanium (Ge) oxide, and combinations thereof, as well as lithium.
[0039] A content of chlorine (Cl) in the solid electrolyte layer may be greater than a content of fluorine (F) in the solid electrolyte layer.
[0040] Advantageous Effects of the Invention
[0041] According to the all-solid-state battery according to the embodiment, the covering layer or the edge layer includes a material having low ionic conductivity, high impedance resistance, and low electronic conductivity, so that the all-solid-state battery has improved reliability by effectively preventing the penetration of external moisture, and has excellent moisture-proof function and excellent insulation to prevent battery failure caused by the deposition of lithium (Li) ion precipitates on the negative electrode during battery operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 is a perspective view schematically showing an all-solid-state battery according to an embodiment.
[0043] Figure 2 is along Figure 1 Cross-sectional view of the all-solid-state battery taken along line I-I'.
[0044] Figure 3 It is a schematic diagram showing the Figure 1 An exploded perspective view of a unit cell stacking structure of an all-solid-state battery of the embodiment shown in FIG. DETAILED DESCRIPTION
[0045] Hereinafter, various embodiments of the present invention will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily perform the present invention. The drawings and descriptions are considered to be illustrative and not restrictive in nature. Throughout the specification, the same reference numerals represent the same elements. In addition, the drawings are provided only to make the embodiments disclosed in this specification easy to understand, and the drawings are not interpreted as limiting the spirit disclosed in this specification, and it should be understood that the present invention includes all variants, equivalents and alternatives without departing from the scope and spirit of the present invention. In addition, some of the constituent elements in the drawings are exaggerated, omitted or schematically shown, and the size of each constituent element does not fully reflect the actual size.
[0046] In addition, unless explicitly described to the contrary, the word “comprise” and variations such as “including” or “having”, will be understood to imply the inclusion of stated elements but not the exclusion of any other elements.
[0047] Throughout the specification, "stacking direction" refers to the direction in which constituent elements are stacked in sequence or the "thickness direction" perpendicular to the large surface (main surface) of the sheet-like constituent element, which corresponds to the T-axis direction in the drawings. In addition, "lateral direction" refers to the direction extending from the edge of the sheet-like constituent element in parallel to the large surface (main surface) or the "plane direction", which corresponds to the L-axis direction in the drawings.
[0048] Figure 1 is a perspective view schematically showing an all-solid-state battery according to an embodiment, and Figure 2 is along Figure 1 A cross-sectional view of an all-solid-state battery taken along line II'. Figure 1 and Figure 2 Describe the all-solid-state battery in detail.
[0049] For example, the all-solid-state battery 100 may have a substantially hexahedral shape.
[0050] In this example embodiment, for ease of description, in the all-solid-state battery 100, two surfaces opposite to each other in the thickness direction (T-axis direction) are defined as the first surface and the second surface, and two surfaces connected to the first surface and the second surface and opposite to each other in the length direction (L-axis direction) are defined as the third surface and the fourth surface. For example, the first side surface and the second side surface of the all-solid-state battery 100 may be the third surface and the fourth surface.
[0051] The all-solid-state battery 100 according to the present embodiment includes electrode layers 120 and 140 and a solid electrolyte layer 130 adjacent to the electrode layers 120 and 140 in a stacking direction. The electrode layers 120 and 140 may include a positive electrode layer 120 and a negative electrode layer 140, and may mainly include current collectors 123 and 143 and active material layers 121, 122, 141, and 142 coated on at least one surface of the current collectors 123 and 143.
[0052] The positive electrode layer 120 may be formed by coating the positive electrode active material layers 121 and 122 on at least one surface of the positive electrode collector 123, and the negative electrode layer 140 may be formed by coating the negative electrode active material layers 141 and 142 on at least one surface of the negative electrode collector 143. For example, the uppermost electrode layer in the stacking direction may be formed by coating the positive electrode active material layer 122 on one surface of the positive electrode collector 123, and the lowermost electrode layer may be formed by coating the negative electrode active material layer 141 on one surface of the negative electrode collector 143. In addition, the electrode layer located between the uppermost end and the lowermost end may be formed by coating the positive electrode active material layers 121 and 122 on both surfaces of the positive electrode collector 123, or by coating the negative electrode active material layers 141 and 142 on both surfaces of the negative electrode collector 143.
[0053] The positive electrode active material layers 121 and 122 may include a positive electrode active material, and optionally, may include a solid electrolyte. In addition, optionally, the positive electrode active material layers 121 and 122 may further include an additive such as a binder or a conductive agent.
[0054] For example, the positive electrode active material is not particularly limited as long as it can ensure sufficient capacity of the all-solid-state battery 100. For example, the positive electrode active material may include lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium manganese oxide, or a combination thereof.
[0055] For example, the positive electrode active material may be a compound represented by the following chemical formula: Li a A 1-b M b D2 (where 0.90≤a≤1.8, 0≤b≤0.5); Li a E 1-b M b O 2-c D c (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); LiE 2- b M b O 4-c D c (where 0≤b≤0.5, 0≤c≤0.05); Lia Ni 1-b-c Co b M c D α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α≤2); Li a Ni 1-b-c Co b M c O 2-α X α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni 1-b-c CO b M c O 2-α X2 (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni 1-b-c Mn b M c D α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α≤2); Li a Ni 1-b-c Mn b M c O 2-α X α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni 1-b-c Mn b M c O 2-α X2 (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni b E c G d O2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0.001≤d≤0.1); Li a Ni b Co c Mn d GeO2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, 0.001≤e≤0.1); Li a NiGbO2 (where 0.90≤a≤1.8, 0.001≤b≤0.1); Li aCoGbO2 (where 0.90≤a≤1.8, 0.001≤b≤0.1); Li a MnGbO2 (where 0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn2GbO4 (where 0.90≤a≤1.8, 0.001≤b≤0.1); QO2; QS2; LiQS2; V2O5; LiV2O2; LiRO2; LiNiVO4; Li (3-f) J2(PO4)3(0≤f≤2);Li (3-f) Fe2(PO4)3 (where 0≤f≤2) and LiFePO4, wherein, in the above chemical formula, A is Ni, Co or Mn; M is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V or a rare earth element; D is O, F, S or P; E is Co or Mn; X is F, S or P; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr or V; Q is Ti, Mo or Mn; R is Cr, V, Fe, Sc or Y; and J is V, Cr, Mn, Co, Ni or Cu.
[0056] The positive electrode active material can also be LiCoO2, LiMn x O 2x (where x=1 or 2), LiNi 1-x Mn x O 2x (Among them, 0 <x<1)、LiNi 1-x-y Co x Mn y O2 (wherein 0≤x≤0.5 and 0≤y≤0.5), LiFePO4, TiS2, FeS2, TiS3 or FeS3.
[0057] The solid electrolyte may be a solid electrolyte usable in the solid electrolyte layer 130 described later. The solid electrolyte may serve as an ion conduction path in the positive electrode layer 120, whereby the interface resistance may be reduced.
[0058] Based on 100 parts by weight of the total amount of the positive electrode active material, the content of the solid electrolyte may be greater than or equal to 0.1 parts by weight, greater than or equal to 1 part by weight, or greater than or equal to 10 parts by weight, and less than or equal to 80 parts by weight, less than or equal to 60 parts by weight, or less than or equal to 50 parts by weight.
[0059] The conductive agent is not particularly limited as long as it has conductivity and does not cause chemical changes in the all-solid-state battery 100. For example, examples of the conductive agent may include: graphite, such as natural graphite and artificial graphite; carbon-based substances, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and summer black; conductive fibers, such as carbon fibers and metal fibers; carbon fluorides; metal powders, such as aluminum powders and nickel powders; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive materials such as polyphenylene derivatives.
[0060] The conductive agent may be included in an amount of 1 to 10 parts by weight, for example, 2 to 5 parts by weight, based on 100 parts by weight of the positive electrode active material. When the conductive agent content is within the above range, the final electrode may have excellent conductive properties.
[0061] The binder can be used to improve the bonding strength between the active material and the conductive agent. The binder may include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene copolymer (EPDM), sulfonated EPDM, styrene butadiene rubber, fluororubber or various copolymers.
[0062] The binder may be present in an amount of 1 to 50 parts by weight, for example, 2 to 5 parts by weight, based on 100 parts by weight of the positive electrode active material. When the binder content satisfies the above range, the active material layer may have high bonding strength.
[0063] A porous material such as a net or mesh shape may be used as the positive current collector 123, and a porous metal plate such as stainless steel, nickel, or aluminum may be used as the positive current collector 123. In addition, the positive current collector 123 may be coated with an oxidation-resistant metal film or alloy film to prevent oxidation.
[0064] The negative electrode active material layers 141 and 142 may include a negative electrode active material, and optionally, may include a solid electrolyte. In addition, the negative electrode active material layers 141 and 142 may further include an additive such as a binder or a conductive agent, optionally.
[0065] The negative electrode active material may be a carbon-based material, silicon, silicon oxide, silicon-based alloy, silicon-carbon-based material composite, tin, tin-based alloy, tin-carbon composite, metal oxide, or a combination thereof, and may include lithium metal and / or lithium metal alloy.
[0066] The lithium metal alloy may include lithium and a metal / metalloid capable of alloying with lithium. For example, the metal / metalloid capable of alloying with lithium may include Si, Sn, Al, Ge, Pb, Bi, Sb, Si-Y alloy (where Y is an alkali metal, alkaline earth metal, Group 13 to Group 16 element, transition metal, rare earth element, or a combination thereof, and does not include Si), Sn-Y alloy (where Y is an alkali metal, alkaline earth metal, Group 13 to Group 16 element, transition metal, or a transition metal oxide such as lithium titanate (Li4Ti5O 12 ) rare earth element, or a combination thereof, and does not include Sn) or M n O x (0 < x ≤ 2).
[0067] The element Y may be Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, or a combination thereof.
[0068] In addition, the oxide of the metal / metalloid capable of alloying with lithium may be lithium titanate, vanadium oxide, lithium vanadium oxide, SnO2, SiO x (0 < x < 2), etc. For example, the negative electrode active material may include one or more elements selected from the elements of Group 13 to Group 16 of the periodic table. For example, the negative electrode active material may include one or more elements selected from the group consisting of Si, Ge, and Sn.
[0069] The carbon-based material may be crystalline carbon, amorphous carbon, or a mixture thereof. The crystalline carbon may include graphite, such as natural graphite or artificial graphite in amorphous form, plate form, flake form, spherical form, or fiber form. In addition, the amorphous carbon may include soft carbon (low-temperature calcined carbon) or hard carbon, mesophase pitch carbonized product, calcined coke, graphene, carbon black, fullerene soot, carbon nanotube, carbon fiber, etc.
[0070] Silicon may be Si, SiO x (0 < x < 2, for example, 0.5 to 1.5), Sn, SnO2, silicon-containing metal alloy, or a mixture thereof. For example, the silicon-containing metal alloy may include one or more of Al, Sn, Ag, Fe, Bi, Mg, Zn, In, Ge, Pb, and Ti, and silicon.
[0071] The solid electrolyte may be a solid electrolyte usable in the solid electrolyte layer 130 described later. The solid electrolyte may serve as an ion conduction path in the negative electrode layer 140, and thereby, the interface resistance may be reduced.
[0072] Based on 100 parts by weight of the total amount of the negative electrode active material, the content of the solid electrolyte may be greater than or equal to 0.1 parts by weight, greater than or equal to 1 part by weight, or less than or equal to 10 parts by weight, less than or equal to 80 parts by weight, less than or equal to 60 parts by weight, or less than or equal to 50 parts by weight.
[0073] Optionally, the negative electrode active material layers 141 and 142 may further include a conductive agent and a binder as described with respect to the positive electrode active material layers 121 and 122 .
[0074] The negative electrode current collector 143 may be a mesh or a mesh-like porous body and a porous metal plate such as stainless steel, nickel or aluminum. In addition, the negative electrode current collector 143 may be coated with an oxidation-resistant metal film or alloy film to prevent oxidation.
[0075] The solid electrolyte layer 130 may be interposed and stacked between the positive electrode layer 120 and the negative electrode layer 140. Therefore, the solid electrolyte layer 130 may be disposed adjacently between the positive electrode active material layers 121 and 122 of the positive electrode layer 120 and the negative electrode active material layers 141 and 142 of the negative electrode layer 140 in the stacking direction. Therefore, in the all-solid-state battery 100, a plurality of positive electrode layers 120 and a plurality of negative electrode layers 140 may be disposed alternately, and a plurality of solid electrolyte layers 130 may be interposed and stacked between them. The all-solid-state battery 100 is a stacked all-solid-state battery 100 manufactured by alternately stacking a plurality of positive electrode layers 120 and a plurality of negative electrode layers 140, and interposing a plurality of solid electrolyte layers 130 between them to provide a unit stack, and then firing them together.
[0076] The solid electrolyte layer 130 may include an inorganic solid electrolyte including an oxide-based solid electrolyte, a sulfide-based solid electrolyte, or a combination thereof.
[0077] The oxide-based solid electrolyte may be a garnet-type electrolyte, a sodium superionic conductor (NASICON)-type electrolyte, a lithium superionic conductor (LISICON)-type electrolyte, a perovskite-type electrolyte, a lithium phosphorus oxygen nitrogen (LiPON)-type electrolyte, or an amorphous (glass) electrolyte.
[0078] The garnet-based solid electrolyte may include Li a La b Zr c O 12 Lithium lanthanum zirconium oxide (LLZO) (such as Li7La3Zr2O 12), and the sodium superionic conductor (NASICON)-based solid electrolyte may include those in which Ti is introduced into Li 1+ x Al x M 2-x (PO4)3 (LAMP) (0 < x < 2, M is Zr, Ti or Ge) type compounds of lithium aluminum titanium phosphate (LATP) (Li 1+x Al x Ti 2-x (PO4)3 (0 < x < 1)), lithium aluminum germanium phosphate (LAGP) represented by Li 1+x Al x Ge 2-x (PO4)3 (0 < x < 1) (such as Li 1.3 Al 0.3 Ti 1.7 (PO4)3) and / or lithium zirconium phosphate (LZP) (LiZr2(PO4)3).
[0079] In addition, the lithium superionic conductor (LISICON)-based solid electrolyte may include a solid solution oxide represented by xLi3AO4-(1-x)Li4BO4 (where A is P, As or V, and B is Si, Ge or Ti), such as Li4Zn(GeO4)4, Li 10 GeP2O 12 (LGPO), Li 3.5 Si 0.5 P 0.5 O4 or Li 10.42 Si(Ge) 1.5 P 1.5 Cl 0.08 O 11.92 , or a solid solution sulfide represented by Li 4-x M 1-y M' y S4 (where M is Si or Ge, and M' is P, Al, Zn or Ga), such as Li2S-P2S5, Li2S-SiS2, Li2S-SiS2-P2S5 or Li2S-GeS2.
[0080] The perovskite-based solid electrolyte may include lithium lanthanum titanate (LLTO) represented by Li 3x La 2 / 3-x □ 1 / 3-2x TiO3 (0 < x < 0.16, □: vacancy), such as Li 1 / 8 La 5 / 8 TiO3. The lithium phosphorus oxynitride (LiPON)-based solid electrolyte may include lithium phosphorus oxynitride, such as Li 2.8 PO 3.3 N0.46 .
[0081] Examples of amorphous electrolytes include Li2O-B2O3-SiO2, Li2O-B2O3-P2O5, Li3BO3-Li2SO4, or Li3BO3-Li2CO3.
[0082] For example, the oxide-based solid electrolyte may include glass or glass ceramic as a lithium ion conductor, and may include glass ceramic so that lithium (Li) ion conductivity can be further improved. When the solid electrolyte layer 130 includes glass or glass ceramic, the stability of the solid electrolyte layer 130 to atmospheric moisture can be improved.
[0083] Herein, glass refers to a crystallographic amorphous material in which a halo is observed in X-ray diffraction, electron beam diffraction, etc. Glass ceramics (or crystallized glass) refers to a mixture of amorphous crystals and crystalline crystals in which peaks and halos are observed in X-ray diffraction, electron beam diffraction, etc.
[0084] In terms of improved performance of the all-solid-state battery 100, the solid electrolyte may have a thickness of 1.0×10 -7 The lithium (Li) ion conductivity of the solid electrolyte is measured in the same manner as the method of measuring the lithium (Li) ion conductivity of the edge layer 150 or the cover layer 160, except that the sample for measurement is prepared in the following manner: the solid electrolyte layer 130 is exposed by ion milling, polishing, etc. in the all-solid-state battery 100 and the sample is used.
[0085] The glass or glass ceramic included in the solid electrolyte layer 130 may be sintered. The sintering of the glass or glass ceramic may be performed at 550° C. or less (eg, 300° C. to 550° C., or 300° C. to 500° C.).
[0086] When the sintering of the glass or glass ceramic is performed at 550° C. or less, since the loss of the carbon material is suppressed during the sintering process, the carbon material can be used as a negative electrode active material, and the energy density of the all-solid-state battery 100 is also improved. In addition, when the positive electrode active material layers 121 and 122 include a conductive agent, the carbon material can be used as a conductive agent to form a good electron conduction path in the positive electrode active material layers 121 and 122, thereby improving the conductivity of the positive electrode active material layers 121 and 122. In addition, even when the negative electrode active material layers 141 and 142 include a conductive agent, the carbon material can be used as a conductive agent, thereby improving the conductivity of the negative electrode active material layers 141 and 142.
[0087] When the sintering temperature of the glass or glass ceramic is greater than 550° C., the solid electrolyte reacts with the electrode active material during the sintering process to form byproducts and thus deteriorate the characteristics of the all-solid-state battery 100. In addition, when the sintering temperature is 550° C. or less, which corresponds to low-temperature sintering, the type of electrode active material can be selected within a wider range, thereby improving the design freedom of the all-solid-state battery 100.
[0088] When the sintering temperature of glass or glass ceramic is 300° C. or more, an organic binder (such as acrylic resin, etc.) that may be included in the electrode precursor and / or the precursor of the solid electrolyte layer 130 may be lost during the sintering process.
[0089] The glass or glass-ceramic may include lithium (Li) oxide and lithium chloride (LiCl), respectively.
[0090] The glass or glass ceramic including lithium (Li) oxide has a sintering temperature of 550° C. or less, high heat shrinkage, and excellent fluidity. Therefore, the reaction between the solid electrolyte layer 130 and the positive electrode active material layers 121 and 122 and the reaction between the solid electrolyte layer 130 and the negative electrode active material layers 141 and 142 can be suppressed. In addition, the interface resistance can be reduced by forming a satisfactory interface between the positive electrode active material layers 121 and 122 and the solid electrolyte layer 130 and between the negative electrode active material layers 141 and 142 and the solid electrolyte layer 130.
[0091] In addition, when the glass or glass ceramic includes lithium chloride (LiCl), a glass having a thickness of 1.0×10 -6 S / cm high ion conductivity battery.
[0092] The glass or glass ceramic may further include silicon (Si) oxide, boron (B) oxide, phosphorus (P) oxide, germanium (Ge) oxide, or a combination thereof. The glass or glass ceramic including silicon (Si) oxide, boron (B) oxide, phosphorus (P) oxide, germanium (Ge) oxide, or a combination thereof in addition to lithium (Li) oxide and lithium chloride (LiCl) has a sintering temperature of 300° C. to 550° C., high thermal shrinkage, and excellent fluidity, thereby reducing interface resistance and thus improving the energy density of the all-solid-state battery 100.
[0093] In order to reduce the sintering temperature of the solid electrolyte, the content of lithium (Li) oxide (Li2O) may be 20 mol% to 75 mol%, e.g., 30 mol% to 75 mol%, 40 mol% to 75 mol%, or 50 mol% to 75 mol%, based on the total amount of the glass or glass ceramic.
[0094] The content of lithium chloride (LiCl) based on the total amount of glass or glass ceramic may be 3 mol% to 22 mol%, for example, 3 mol% to 6 mol% or 18 mol% to 22 mol%. When the content of lithium chloride (LiCl) is less than 3 mol%, it may be difficult to ensure high ion conductivity, and when the content of lithium chloride (LiCl) is greater than 22 mol%, deliquescent properties may be deteriorated.
[0095] When the glass or glass ceramic further includes silicon (Si) oxide (SiO 2 ), the content of silicon (Si) oxide may be 0 mol % to 70 mol %, for example, 0 mol % to 12 mol % or 15 mol % to 30 mol %, based on the total amount of the glass or glass ceramic.
[0096] When the glass or glass ceramic further includes boron (B) oxide (B2O3), the content of the boron (B) oxide may be 0 mol% to 60 mol%, for example, 5 mol% to 15 mol% or 17 mol% to 35 mol%, based on the total amount of the glass or glass ceramic.
[0097] When the glass or glass ceramic further includes phosphorus (P) oxide (P2O5), the content of phosphorus (P) oxide may be 0 mol% to 50 mol%, for example, 8 mol% to 17 mol% or 20 mol% to 40 mol%, based on the total amount of the glass or glass ceramic.
[0098] When the glass or glass ceramic further includes germanium (Ge) oxide (GeO 2 ), the content of the germanium (Ge) oxide may be 0 mol % to 80 mol %, for example, 0 mol % to 3 mol % or 5 mol % to 8 mol %, based on the total amount of the glass or glass ceramic.
[0099] The content of each oxide in the glass or glass ceramic is the content of each oxide based on the total amount (mol) of lithium (Li) oxide, lithium chloride (LiCl), silicon (Si) oxide, boron (B) oxide, phosphorus (P) oxide and germanium (Ge) oxide (e.g., the content (mol) ratio of each oxide, which is expressed as a percentage (mol%)). The content of each oxide can be measured by using inductively coupled plasma atomic emission spectrometry (ICP-AES) or the like.
[0100] As required, glass or glass ceramics may also include additive elements. Examples of additive elements may include Na (sodium), Mg (magnesium), Al (aluminum), K (potassium), Ca (calcium), Ti (titanium), V (vanadium), Cr (chromium), Mn (manganese), Fe (iron), Co (cobalt), Ni (nickel), Cu (copper), Zn (zinc), Ga (gallium), Se (selenium), Rb (rubidium), S (sulfur), Y (yttrium), Zr (zirconium), Nb (niobium), Mo (molybdenum), Ag (silver), In (indium), Sn (tin), Sb (antimony), Cs (cesium), Ba (vanadium), Hf (hafnium), Ta (tantalum), W (tungsten), Pb (lead), Bi (bismuth), Au (gold), La (lanthanum), Nd (neodymium), Eu (europium) or a combination thereof. Glass or glass ceramics may include at least one of these additive elements in the form of oxides.
[0101] The glass or glass ceramic included in the solid electrolyte layer 130 may have a thickness of 1×10 -3 S / cm ionic conductivity. The ionic conductivity can be measured at a temperature of 25°C. The ionic conductivity can be greater than or equal to 1×10 -3 S / cm, greater than or equal to 2×10 -3 S / cm, greater than or equal to 3×10 -3 S / cm, greater than or equal to 4×10 -3 S / cm or greater than or equal to 5×10 -3 S / cm, and the upper limit of the ion conductivity is not particularly limited. When a solid electrolyte satisfying the range of ion conductivity is used, the all-solid-state battery 100 can exhibit high output.
[0102] The edge layer 150 may be disposed along the edge of the positive electrode layer 120 and the edge of the negative electrode layer 140. The edge layer 150 may be disposed on the solid electrolyte layer 130, and may be formed laterally adjacent to the edges of the positive electrode active material layers 121 and 122 or the edges of the negative electrode active material layers 141 and 142. Therefore, the edge layer 150 may be disposed on the same layer as the positive electrode layer 120 and on the same layer as the negative electrode layer 140.
[0103] Figure 3 It is a schematic diagram showing the Figure 1 An exploded perspective view of a unit cell stacking structure of an all-solid-state battery 100 of the embodiment shown in FIG.
[0104] Reference Figure 3In this embodiment, the positive electrode layer 120 and the edge layer 150 stacked on the solid electrolyte layer 130 form a positive electrode unit 102, and the negative electrode layer 140 and the edge layer 150 stacked on another solid electrolyte layer 130 can form a negative electrode unit 104. A plurality of positive electrode units 102 and a plurality of negative electrode units 104 are alternately stacked and combined to form a unit stack of the all-solid-state battery 100 according to the present embodiment.
[0105] Specifically, the positive electrode unit 102 may be constructed by sequentially stacking a positive electrode active material layer 121, a positive electrode collector 123 and a positive electrode active material layer 122 on a solid electrolyte layer 130 and forming an edge layer 150 on the same layer as the positive electrode active material layers 121 and 122 and the positive electrode collector 123 to surround the edges of the positive electrode active material layers 121 and 122 and the positive electrode collector 123.
[0106] In addition, the negative electrode unit 104 may be constructed by sequentially stacking a negative electrode active material layer 142, a negative electrode collector 143 and a negative electrode active material layer 141 on the solid electrolyte layer 130 and forming an edge layer 150 on the same layer as the negative electrode active material layers 141 and 142 and the negative electrode collector 143 to surround the edges of the negative electrode active material layers 141 and 142 and the negative electrode collector 143.
[0107] The positive electrode layer 120 , the solid electrolyte layer 130 , the negative electrode layer 140 , and the edge layer 150 are stacked as described above to constitute a unit stack of the all-solid-state battery 100 , and the cover layer 160 is provided on the outer surface of the unit stack of the all-solid-state battery 100 .
[0108] For example, the cover layer 160 may surround the surface of the unit stack, so that one end of the positive electrode layer 120 may be exposed to the first surface of the unit stack (or in contact with the first surface of the unit stack or extending from the first surface of the unit stack) and connected to one external electrode 112, and one end of the negative electrode layer 140 may be exposed to the second surface of the unit stack (or in contact with the second surface of the unit stack or extending from the second surface of the unit stack) and connected to the other external electrode 114, for example, the cover layer 160 may be provided on the third surface and the fourth surface other than the first surface and the second surface of the unit stack, or may be provided on the outer surfaces of the electrode layer 120 at the top and the negative electrode layer 140 at the bottom of the unit stack in the stacking direction. Herein, the solid electrolyte layer 130 may be provided between the cover layer 160 and the positive electrode layer 120 adjacent thereto or may be provided between the cover layer 160 and the negative electrode layer 140 adjacent thereto.
[0109] The edge layer 150 and / or the cover layer 160 include glass or glass ceramics. By surrounding the surface of the all-solid-state battery 100 with the edge layer 150 and / or the cover layer 160 including these materials, moisture penetration into the all-solid-state battery 100 can be suppressed. Therefore, the moisture resistance of the all-solid-state battery 100 can be improved.
[0110] The glass or glass ceramic included in the edge layer 150 and / or the cover layer 160 may include lithium fluoride (LiF).
[0111] Compared with lithium chloride (LiCl), lithium fluoride (LiF) has high density and low water solubility, and is insoluble, thus effectively preventing the penetration of external moisture. In addition, compared with lithium chloride (LiCl) under the firing condition of 450°C to 500°C, lithium fluoride (LiF) has low ion conductivity and equal thermal shrinkage density.
[0112] In other words, when the covering layer 160 and / or the edge layer 150 include glass or glass ceramics containing lithium fluoride (LiF), lithium fluoride (LiF) has low ionic conductivity, high impedance resistance and low electronic conductivity, and therefore, can effectively prevent the penetration of external moisture and thus exhibit an excellent moisture-proof function. In addition, it has excellent insulation and thus can prevent defects of the all-solid-state battery 100 caused by the deposition of lithium (Li) ion precipitates on the negative electrode during operation of the all-solid-state battery 100, thereby improving the reliability of the all-solid-state battery 100.
[0113] The glass or glass ceramic included in the edge layer 150 and / or the cover layer 160 may further include lithium (Li) oxide, silicon (Si) oxide, boron (B) oxide, phosphorus (P) oxide, germanium (Ge) oxide, or a combination thereof. The glass or glass ceramic including lithium (Li) oxide, silicon (Si) oxide, boron (B) oxide, phosphorus (P) oxide, germanium (Ge) oxide, or a combination thereof and lithium fluoride (LiF) has a sintering temperature of 300° C. to 550° C., high thermal shrinkage, and excellent fluidity, thereby reducing interface resistance and improving the energy density of the all-solid-state battery 100.
[0114] The content of lithium fluoride (LiF) may be 5 mol% to 15 mol%, for example, 5 mol% to 10 mol% or 10 mol% to 15 mol%, based on the total amount of the glass or glass ceramic. When the content of lithium fluoride (LiF) is less than 5 mol%, the sintering temperature characteristics may be deteriorated, and when the content of lithium fluoride (LiF) is greater than 15 mol%, a loss of clarity may occur.
[0115] In order to reduce the sintering temperature of the solid electrolyte, the content of lithium (Li) oxide (Li2O) may be 20 mol% to 75 mol%, e.g., 30 mol% to 75 mol%, 40 mol% to 75 mol%, or 50 mol% to 75 mol%, based on the total amount of the glass or glass ceramic.
[0116] When the glass or glass ceramic further includes silicon (Si) oxide (SiO 2 ), the content of silicon (Si) oxide may be 0 mol % to 70 mol %, for example, 0 mol % to 12 mol % or 15 mol % to 30 mol %, based on the total amount of the glass or glass ceramic.
[0117] When the glass or glass ceramic further includes boron (B) oxide (B2O3), the content of the boron (B) oxide may be 0 mol% to 60 mol%, for example, 5 mol% to 15 mol% or 17 mol% to 35 mol%, based on the total amount of the glass or glass ceramic.
[0118] When the glass or glass ceramic further includes phosphorus (P) oxide (P2O5), the content of phosphorus (P) oxide may be 0 mol% to 50 mol%, for example, 8 mol% to 17 mol% or 20 mol% to 40 mol%, based on the total amount of the glass or glass ceramic.
[0119] When the glass or glass ceramic further includes germanium (Ge) oxide (GeO 2 ), the content of the germanium (Ge) oxide may be 0 mol % to 80 mol %, for example, 0 mol % to 3 mol % or 5 mol % to 8 mol %, based on the total amount of the glass or glass ceramic.
[0120] The content of each oxide in the glass or glass ceramic is the content of each oxide based on the total amount (mol) of lithium fluoride (LiF), lithium (Li) oxide, silicon (Si) oxide, boron (B) oxide, phosphorus (P) oxide and germanium (Ge) oxide (e.g., the content (mol) ratio of each oxide, which is expressed as a percentage (mol%)). The content of each oxide can be measured by using inductively coupled plasma atomic emission spectrometry (ICP-AES) or the like.
[0121] As required, glass or glass ceramics may also include additive elements. Examples of additive elements may include Na (sodium), Mg (magnesium), Al (aluminum), K (potassium), Ca (calcium), Ti (titanium), V (vanadium), Cr (chromium), Mn (manganese), Fe (iron), Co (cobalt), Ni (nickel), Cu (copper), Zn (zinc), Ga (gallium), Se (selenium), Rb (rubidium), S (sulfur), Y (yttrium), Zr (zirconium), Nb (niobium), Mo (molybdenum), Ag (silver), In (indium), Sn (tin), Sb (antimony), Cs (cesium), Ba (vanadium), Hf (hafnium), Ta (tantalum), W (tungsten), Pb (lead), Bi (bismuth), Au (gold), La (lanthanum), Nd (neodymium), Eu (europium) or a combination thereof. Glass or glass ceramics may include at least one of these additive elements in the form of oxides.
[0122] In order to improve the moisture resistance of the all-solid-state battery 100, the edge layer 150 or the cover layer 160 may have a moisture content of less than or equal to 1 g / m 2 / day (for example, less than or equal to 0.75g / m 2 / day or less than or equal to 0.5g / m 2 / day). The moisture permeability of the edge layer 150 or the covering layer 160 can be measured as follows. First, a portion of the edge layer 150 or the covering layer 160 is sampled as a rectangular plate by ion milling or polishing in the all-solid-state battery 100. Subsequently, the water vapor permeability (23°C, 90% relative humidity (RH)) of the edge layer 150 or the covering layer 160 is measured according to JIS K7129-C (ISO 15106-4).
[0123] In order to prevent the self-discharge of the all-solid-state battery 100, the edge layer 150 or the cover layer 160 may have a thickness less than or equal to 1×10 -8 S / cm (e.g., less than or equal to 1×10 -10 S / cm) of lithium (Li) ion conductivity.
[0124] The lithium (Li) ion conductivity of the edge layer 150 or the cover layer 160 can be measured by an alternating current (AC) impedance method. First, a portion of the edge layer 150 or the cover layer 160 is sampled as a rectangular plate in the all-solid-state battery 100 by ion milling, polishing, etc. Subsequently, electrodes made of gold (Au) are formed at both ends of the obtained sheet to obtain a sample. Then, the alternating current (AC) impedance (frequency: 10 +6 Hz to 10 -1 Hz, voltage: 100 mV, 1000 mV), and then calculate the ionic conductivity.
[0125] In order to prevent the self-discharge of the all-solid-state battery 100, the electronic conductivity of the edge layer 150 or the cover layer 160 may be less than or equal to 1×10 -8 S / cm, for example, less than or equal to 1×10 -10 S / cm.
[0126] The electron conductivity of the edge layer 150 or the cover layer 160 was obtained by preparing a sample in the same method as the method of measuring lithium (Li) ion conductivity and using the sample at room temperature (25° C.) by a 2-terminal method.
[0127] The average thickness of the covering layer 160 may be less than or equal to 50 μm, for example, less than or equal to 40 μm or less than or equal to 30 μm to improve the energy density of the all-solid-state battery 100. The average thickness of the covering layer 160 can be measured as follows. First, a cross section of the covering layer 160 is prepared by ion milling or the like, and a scanning electron microscope (SEM) photograph of the cross section is taken. Subsequently, in the cross-sectional SEM photograph, 10 points are randomly selected, and the thickness of the covering layer 160 at each point is measured and averaged to obtain the arithmetic mean as the average thickness of the covering layer 160.
[0128] As described above, the terminals of the positive current collector 123 and the negative current collector 143 are exposed to both sides of the unit stack of the all-solid-state battery 100 (or are in contact with both sides of the unit stack of the all-solid-state battery 100 or extend from both sides of the unit stack of the all-solid-state battery 100), and the external electrodes 112 and 114 are connected to the exposed terminals and combined with them. In other words, the external electrodes 112 and 114 are connected to the terminals of the positive current collector 123 to form a positive electrode, and further, are connected to the terminals of the negative current collector 143 to form a negative electrode. When the terminals of the positive current collector 123 and the terminals of the negative current collector 143 are configured to be opposite to each other in opposite directions, the external electrodes 112 and 114 may also be located at both sides, respectively.
[0129] Herein, the external electrodes 112 and 114 may cover the cover layer 160 and the side of the unit stack. In other words, when the unit stack is manufactured, the cover layer 160 is formed by firing all together, and then, when the external electrodes 112 and 114 are formed, the external electrodes 112 and 114 may also be located at the side of the cover layer 160. From this point of view, the cover layer 160 is different from the protective layer formed after the external electrodes 112 and 114 are formed.
[0130] The protective layer is disposed on the outer side of the cover layer 160, but covers the band portion extending toward the first side or the second side of the protective layer, and the outer electrodes 112 and 114 may not be located on the side of the protective layer. The protective layer may include an insulating material such as polyolefin (such as polyethylene, polypropylene, etc.), polyester (such as polyethylene terephthalate (PET), etc.), polyurethane, polyimide, etc., for example, a fluorine-based polymer resin.
[0131] The external electrodes 112 and 114 may include conductive metal and glass.
[0132] For example, the conductive metal may include copper (Cu), nickel (Ni), tin (Sn), palladium (Pd), platinum (Pt), gold (Au), silver (Ag), tungsten (W), titanium (Ti), lead (Pb), or alloys thereof.
[0133] The glass component included in the first external electrode 112 and the second external electrode 114 may have a composition in which an oxide is mixed. For example, the glass component may include silicon oxide, boron oxide, aluminum oxide, transition metal oxide, alkali metal oxide, alkaline earth metal oxide, or a combination thereof. Herein, the transition metal may be selected from zinc (Zn), titanium (Ti), copper (Cu), vanadium (V), manganese (Mn), iron (Fe), or nickel (Ni), the alkali metal may be selected from lithium (Li), sodium (Na), or potassium (K), and the alkaline earth metal may be selected from magnesium (Mg), calcium (Ca), strontium (Sr), or barium (Ba).
[0134] The method of forming the first external electrode 112 and the second external electrode 114 is not particularly limited. For example, the method may include immersing the unit stack in a conductive paste including a conductive metal and glass, or screen printing or gravure printing the conductive paste on the surface of the unit stack. In addition, various methods of coating the conductive paste on the surface of the unit stack or transferring a dry film obtained by drying the conductive paste onto the unit stack may be used.
[0135] Mode for carrying out the invention
[0136] Hereinafter, specific examples of the invention are presented. However, the following examples are only intended to specifically describe or explain the invention, and the scope of the invention should not be limited thereto.
[0137] Glass frits having the compositions shown in Table 1 were prepared and fired at 450° C. to 500° C. to prepare each of the glasses or glass ceramics for the cover layers according to the Examples and Comparative Examples.
[0138] The lithium ion conductivity, heat shrinkage density, and water resistance of the prepared cover layer glass or glass ceramic were measured, and the results are shown in Table 1.
[0139] The lithium ion conductivity is measured by an AC impedance method. For example, a sample is prepared by forming electrodes formed using gold (Au) at both sides of a prepared glass or glass ceramic sample, and then the AC impedance (frequency: 10 +6 Hz to 10 -1 Hz, voltage: 100mV, 1000mV) to calculate the ionic conductivity.
[0140] The heat shrink density is calculated by measuring the exact volume and weight using the apparent density measurement method. For example, the heat shrink density can be obtained by measuring the diameter, thickness and weight of a round pellet, and then calculating [weight] / [(thickness / 10)×(diameter / 20)] 2 ×3.141592.
[0141] The water resistance (WVTR) was evaluated by measuring the water vapor transmission rate (23° C., 90% relative humidity (RH)) of a glass or glass ceramic sample according to JIS K7129-C (ISO 15106-4).
[0142] (Table 1)
[0143]
[0144] The lithium chloride (LiCl) used in the comparative example has a boiling point (bp) of 1382°C, a melting point (mp) of 605°C to 614°C, and a density (g / cm 3 ) is 2.068, the molecular weight (g / mol) is 43.39, the water solubility (g / L) (25°C) is 84.3 g / 100 mL (therefore it is water-soluble) and the ethanol solubility (g / 100 g) (25°C) is 24.28. On the other hand, lithium fluoride (LiF) used in the example has a boiling point (bp) of 1676°C, a melting point (mp) of 845°C, and a density (g / cm 3 ) is 2.64, the molecular weight (g / mol) is 25.949 and the water solubility (g / L) (25°C) is 0.134 g / 100 mL, so it is insoluble.
[0145] In addition, the glass or glass ceramic prepared in the example has an opaque appearance, a specific gravity of 2.1, a hardness of 5.5, a glass transition temperature (°C) of 410°C to 425°C, a softening point (°C) of 430°C to 450°C, a crystallization temperature (°C) of 495°C, a mass reduction-starting temperature (°C) of 120°C, and a thermal expansion coefficient (1 / °C) of 0.7×10 -5 Up to 9×10 -5 And the firing shrinkage (%) is 92.
[0146] Therefore, compared with lithium chloride (LiCl), lithium fluoride (LiF) has high density and low water solubility, and is therefore insoluble, and thus effectively prevents external moisture penetration. In addition, under the firing condition of 450°C to 500°C, lithium fluoride (LiF) has low ion conductivity and the same thermal shrinkage density as lithium chloride (LiCl).
[0147] In other words, since lithium fluoride (LiF) has low ion conductivity, high impedance resistance, and low electronic conductivity, when the covering layer or the edge layer includes glass or glass ceramics containing lithium fluoride (LiF), the all-solid-state battery can effectively prevent the penetration of external moisture to ensure excellent moisture-proof function, and in addition, can effectively prevent battery defects caused by the deposition of lithium (Li) ion precipitates on the negative electrode during the operation of the all-solid-state battery to improve battery reliability.
[0148] While the present invention has been described in conjunction with what are presently considered to be practical example embodiments, it will be understood that the invention is not limited to the disclosed embodiments, but is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
[0149] <Description of Reference Numerals>
[0150] 100: All-solid-state battery
[0151] 102: Positive electrode unit
[0152] 104: Negative electrode unit
[0153] 112, 114: External electrode
[0154] 120: Positive electrode layer
[0155] 121, 122: Positive electrode active material layer
[0156] 123: Positive electrode current collector
[0157] 130: Solid electrolyte layer
[0158] 140: Negative electrode layer
[0159] 141, 142: Negative electrode active material layer
[0160] 143: Negative electrode current collector
[0161] 150: Edge layer
[0162] 160: Overlay
[0163] Industrial Applicability
[0164] The present disclosure relates to an all-solid-state battery having improved reliability by effectively preventing penetration of external moisture and having excellent moisture-proof function and excellent insulation to prevent battery failure caused by deposition of lithium (Li) ion precipitates on a negative electrode during battery operation.
Claims
1. An all-solid-state battery, comprising: a unit stack including a solid electrolyte layer and a positive electrode layer and a negative electrode layer, wherein the positive electrode layer and the negative electrode layer are arranged so that the solid electrolyte layer is interposed between the positive electrode layer and the negative electrode layer; as well as a covering layer, located on the outer surface of the unit stack, The cover layer includes glass containing lithium fluoride (LiF) or glass ceramic containing lithium fluoride (LiF).
2. The all-solid-state battery according to claim 1, wherein: The glass or the glass ceramic includes lithium fluoride (LiF) and lithium (Li) oxide.
3. The all-solid-state battery according to claim 2, wherein: The glass or the glass ceramic further includes silicon (Si) oxide, boron (B) oxide, phosphorus (P) oxide, germanium (Ge) oxide, or a combination thereof.
4. The all-solid-state battery according to claim 3, wherein: Based on the total amount of the glass or the glass ceramic, the glass or the glass ceramic includes 5 mol% to 15 mol% of lithium fluoride (LiF), 20 mol% to 75 mol% of lithium (Li) oxide, 0 mol% to 70 mol% of silicon (Si) oxide, 0 mol% to 60 mol% of boron (B) oxide, 0 mol% to 50 mol% of phosphorus (P) oxide and 0 mol% to 80 mol% of germanium (Ge) oxide.
5. The all-solid-state battery according to claim 1, wherein: The solid electrolyte layer includes glass including lithium (Li) oxide and lithium chloride (LiCl) or glass ceramic including lithium (Li) oxide and lithium chloride (LiCl).
6. The all-solid-state battery according to claim 5, wherein: The glass or the glass ceramic included in the solid electrolyte layer further includes silicon (Si) oxide, boron (B) oxide, phosphorus (P) oxide, germanium (Ge) oxide, or a combination thereof.
7. The all-solid-state battery according to claim 6, wherein: The glass or the glass ceramic included in the solid electrolyte layer includes 3 mol % to 22 mol % of lithium chloride (LiCl), 20 mol % to 75 mol % of lithium (Li) oxide, 0 mol % to 70 mol % of silicon (Si) oxide, 0 mol % to 60 mol % of boron (B) oxide, 0 mol % to 50 mol % of phosphorus (P) oxide and 0 mol % to 80 mol % of germanium (Ge) oxide, based on the total amount of the glass or the glass ceramic included in the solid electrolyte layer.
8. The all-solid-state battery according to claim 1, wherein: The cover layer is provided on an outer surface of the positive electrode layer or the negative electrode layer located at the outermost side in the stacking direction of the unit stack.
9. The all-solid-state battery according to claim 8, further comprising: A solid electrolyte layer is provided between the cover layer and the positive electrode layer adjacent to the cover layer or between the cover layer and the negative electrode layer adjacent to the cover layer.
10. The all-solid-state battery according to claim 1, wherein: The unit stack further includes an edge layer disposed laterally adjacent to edges of the positive electrode layer and the negative electrode layer, and The edge layer comprises a glass containing lithium fluoride (LiF) or a glass ceramic containing lithium fluoride (LiF).
11. An all-solid-state battery, comprising: A unit stack, comprising: Solid electrolyte layer; a positive electrode layer and a negative electrode layer, arranged so that the solid electrolyte layer is interposed between the positive electrode layer and the negative electrode layer; and an edge layer, arranged laterally adjacent to the edges of the positive electrode layer and the negative electrode layer, The edge layer comprises glass containing lithium fluoride (LiF) or glass ceramic containing lithium fluoride (LiF).
12. The all-solid-state battery according to claim 11, wherein: Based on the total amount of the glass or the glass ceramic, the glass or the glass ceramic includes 5 mol% to 15 mol% of lithium fluoride (LiF), 20 mol% to 75 mol% of lithium (Li) oxide, 0 mol% to 70 mol% of silicon (Si) oxide, 0 mol% to 60 mol% of boron (B) oxide, 0 mol% to 50 mol% of phosphorus (P) oxide and 0 mol% to 80 mol% of germanium (Ge) oxide.
13. The all-solid-state battery according to claim 11, wherein: The solid electrolyte layer includes glass or glass ceramic, and the glass or the glass ceramic includes 3 mol% to 22 mol% of lithium chloride (LiCl), 20 mol% to 75 mol% of lithium (Li) oxide, 0 mol% to 70 mol% of silicon (Si) oxide, 0 mol% to 60 mol% of boron (B) oxide, 0 mol% to 50 mol% of phosphorus (P) oxide and 0 mol% to 80 mol% of germanium (Ge) oxide, based on the total amount of the glass or the glass ceramic.
14. The all-solid-state battery according to claim 11, wherein: The edge layer extends along an edge of an electrode active material layer of the positive electrode layer or the negative electrode layer.
15. The all-solid-state battery according to claim 14, wherein: The edge layer is stacked on the solid electrolyte layer. 16 . The all-solid-state battery according to claim 11 , further comprising a cover layer located on an outer surface of the unit stack.
17. The all-solid-state battery according to claim 1 or 16, wherein: A first external electrode is disposed adjacent to the unit stack and one side of the cover layer and connected to the positive electrode layer, and A second external electrode is disposed adjacent to the unit stack and the other side of the cover layer and is connected to the negative electrode layer.
18. The all-solid-state battery according to claim 17, wherein: The positive electrode layer includes a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, and The negative electrode layer includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector.
19. The all-solid-state battery according to claim 18, wherein: The positive electrode current collector extends toward the one side of the unit stack and is connected to the first external electrode, and The negative electrode collector extends toward the other side of the unit stack and is connected to the second external electrode.
20. An all-solid-state battery, comprising: A unit stack, comprising: multiple solid electrolyte layers; A plurality of positive electrode layers and a plurality of negative electrode layers are alternately arranged with the plurality of solid electrolyte layers interposed between the plurality of positive electrode layers and the plurality of negative electrode layers; and a plurality of edge layers disposed laterally adjacent to edges of the plurality of positive electrode layers and the plurality of negative electrode layers; a covering layer located on an outer surface of the unit stack in a stacking direction of the plurality of positive electrode layers and the plurality of negative electrode layers; and a first external electrode and a second external electrode disposed laterally adjacent to the unit stack and the cover layer and connected to the plurality of positive electrode layers and the plurality of negative electrode layers, respectively; The plurality of edge layers, the cover layer, or both the plurality of edge layers and the cover layer include glass containing lithium fluoride (LiF) or glass ceramic containing lithium fluoride (LiF).